Gledališki učni pristopi in njihova aplikacija v komunikacijski pouk književnosti v osnovni šoli - Lešnik Jeras, Irina (Sodobna pedagogika, 2024)
Theatre pedagogy, a field combining theatre art and pedagogical science, has been gaining ground in the Slovenian educational space in recent years. It is divided into three parts: theatre literacy, which includes the education of the theatre audience; theatrical creation, in which students actively try various theatrical roles; learning with theatrical approaches, where aesthetic as well as educational goals are pursued. The most established theatre learning approaches, theatre and drama in education, enhance the phenomenon of symbolic play with dramaturgy. The aim of the present paper is establishing compatibility of the drama in education which is applied to the Slovenian literature lesson with the already established communicative literature lesson in all three educational periods of elementary school. Theatre is not a compulsory subject in Slovenian primary schools and is traditionally associated with the teaching of the Slovenian, therefore the mentioned connection appears to make sense, which is also confirmed by the multiple case study. Three classroom case studies are based on exploratory, descriptive and causal pedagogical research. We conclude that the teaching approach of drama in education is compatible with the communicative teaching of literature; it mainly affects the development of the segments of reception capacity related to the literary person, time and space.
Keywords: communication model of teaching; didactics of literature; didaktika književnosti; drama in education; drama v izobraževanju; education; gledališka pedagogika; komunikacijski model poučevanja; learning trough theatre approaches; pedagogika; pedagogy; theatre pedagogy; učenje z gledališkimi pristopi; vzgoja in izobraževanje